Varying doses of evening caffeine ingestion have different effects on rowing ergometer performance, sleep quality, and wakefulness scores - Karakulak, Izzet; Yildirim, Ulaş Can; Erkan, Dilara; Karayigit, Raci; Eyuboglu, Ender; Diedhiou, Azize Bingol; Gundem, Mehmet Can; Tuncer, Selin Yildirim; Sar, Halit; Ozen, Gokmen; Akca, Fırat (Frontiers in Nutrition, 2025)
IntroductionThis study investigated the dose-dependent effects of evening caffeine ingestion on rowing performance, sleep quality, and daytime sleepiness in trained male rowers.MethodsUsing a double-blind, randomized, crossover design, 13 university-level rowers (mean age = 22.07 ± 2.21 years; mean body mass = 77.66 ± 6.45 kg) completed four 2,000 m time–trial sessions between 19:00 and 20:00 h under placebo (PLA), low-dose capsule caffeine (3 mg/kg, LDC), moderate-dose capsule caffeine (6 mg/kg, MDC), and high-dose capsule caffeine (9 mg/kg, HDC) conditions. Performance metrics, heart rate, and subjective sleep assessments were collected. Rowing performance was assessed by a standard 2,000 m rowing ergometer (Concept II, United States) time trial. Sleep quality was measured with a numerical rating scale in the morning after each trial, and daytime sleepiness was measured with the Karolinska Sleepiness Scale.ResultsResults indicated significantly improved rowing times and power output with HDC and MDC compared to PLA (p < 0.05), with HDC yielding the most notable enhancements (d = 0.40–0.41). However, these ergogenic benefits were accompanied by significantly impaired sleep quality and elevated daytime sleepiness in both HDC and MDC groups (p < 0.01; d = 1.3–1.5). Notably, adverse effects such as headache, insomnia, and gastrointestinal discomfort were predominantly reported in the HDC condition (p < 0.05). Although LDC offered mild performance improvements with minimal sleep disruption, only the high dose condition exhibited large physiological and perceptual trade-offs.DiscussionThese findings indicate a clear dose–response relationship, wherein higher evening caffeine intake improves performance but has detrimental effects on sleep and recovery markers. Coaches and athletes should carefully balance caffeine dosing against potential recovery costs, especially in evening training or competition contexts.